Small airways in asthma - Čekerevac, Ivan (Medicinski časopis, 2017)
Asthma is a chronic inflammatory lung disease characterized by reversible obstruction of airways and bronchial hyperresponsiveness. In recent years there has been a growing interest in the role of the small airways in asthma and there is increasing evidence that they contribute significantly to the clinical expression of asthma. Numerous studies have shown that inflammation is present in the small airways of patients with asthma and that it may be more intense than that found in the large airways, particularly in severe asthma, nocturnal asthma, coexisting asthma and obesity and asthma in smokers. Currently there is no accepted single lung function parameter to detect small airways dysfunction. Recent data show that impulse oscillometry, nitrogen washout testing and analysis of exhaled NO are promising diagnostic tools to assess involvement of the small airways. The use of corticosteroids in extrafine formulation, whether alone or in fixed combinations with long-acting b2 agonists, improves drug distribution throughout the bronchial tree, enhancing the therapeutic effect with lower doses of drugs. Key words: small airways, asthma, inflammation, peripheral airways.